Separation of heavy metals using aqueous two-phase systems based on choline chloride/urea and betaine/urea deep eutectic solvents - Atefeh Sadeghi; Gholamreza R. Pazuki (Scientific Reports)
Abstract The heavy metals in the effluents of industries threatens the human health. In this research, aqueous two-phase systems based on two deep eutectic solvents, choline chloride/urea and betaine/urea, along with dipotassium hydrogen phosphate, were used as environmentally friendly systems to extract hexavalent chromium. Binodal curves and tie lines were obtained for two systems. The effect of temperature, pH, metal concentration and salt composition was investigated on the extraction efficiency of chromium. Increasing the temperature, the concentration of metal and the amount of salt increased the extraction efficiency. The system consisting of choline chloride/urea had better extraction than other and showed extraction efficiency of 86.82 ± 1.99 at pH = 10 and temperature of 25 ºC and metal concentration of 80 mg/l. the system based on betaine/urea showed extraction efficiency of 89.51 ± 1.69 at pH = 8.9 and temperature of 25 °C and metal concentration of 80 mg/l. Considering the same cost of two systems, the system including betaine/urea was evaluated as a better system for the separation of chromium. These systems were also used to separate lead, cobalt, nickel and cadmium that showed their high tendency to the low phase.